Prevalence and Causes of Skeletal Deformities in Cultured Juvenile Oncorhynchus mykiss: Skeletal Deformities in Cultured Juvenile Oncorhynchus mykiss - Özcan, Filiz (Revista Colombiana de Ciencias Pecuarias, 2025)
Background: Skeletal development and the incidence of skeletal deformities in fish are among the most important problems that need to be solved to increase the success of aquaculture. Skeletal deformities reduce the survival, growth and nutrition of fish. Objective: In this study, skeletal deformations were investigated in juvenile Oncorhynchus mykiss, the most widely farmed trout in Turkey. Methods:Thirty trout farms were visited and 1200 juvenile individuals were collected and analysed. In order to determine the skeletal deformations in the collected samples, the observed deformations were divided into groups. The most common pathological findings in individuals were also evaluated. Results:As a result of the study, the most common skeletal deformation was compression (C) with a rate of 49.83%. When analysed according to regions, the most deformation occurred in the tail lordosis-kyphosis region with a rate of 73.17%. On the other hand, when we analysed the specimens, 61% lordosis was detected. When jaw bone deformities, fin deformities and pterygophore deformities were analysed, jaw bone deformities were found at the highest rate of 12.08%. The most common pathological finding in the samples was swimming disorder (37.58%). Another result was the change in total deformation rate depending on different water temperatures in the farms.Conclusions: According to the results, the highest deformation rate was found to be 19.58% at 13°.The prevalence of deformities indicates that the environmental conditions in which aquaculture practices are carried out should be regulated as well as the deficiencies in the aquaculture management system.